Exosomal Delivery of miR-155 Inhibitor can Suppress Migration, Invasion, and Angiogenesis via PTEN and DUSP14 in Triple-negative Breast Cancer - Razaviyan, Javad; Sirati-Sabet, Majid; Hadavi, Razie; Karima, Saeed; Rajabibazl, Masoumeh; Mohammadi-Yeganeh, Samira (Current Medicinal Chemistry, 2025)
Introduction Triple-Negative Breast Cancer (TNBC) is the most common type of breast cancer (BC). In order to develop effective treatments for TNBC, it is vital to identify potential therapeutic targets. Angiogenesis stimulates tumor growth and metastasis in TNBC, and miR-155 plays a crucial role in this process. The exosome is a nano-sized vesicle that carries many cargoes, including miRNAs. The present study investigated the effect of exosomal delivery of miR-155 antagomir on tumor migration, invasion, and angiogenesis in TNBC. Materials and Methods From MDA-MB-231 cells, exosomes were extracted, characterized, and loaded with miR-155 antagomir using electroporation. The expression of miR-155 and its target genes, including PTEN and DUSP14, was analyzed using RT-qPCR. The wound-healing and transwell assays were used to measure cell migration and invasion. Furthermore, angiogenesis was evaluated by tube formation and chorioallantoic membrane (CAM) assays. Results The results indicated that exosomal delivery of miR-155 antagomir to HUVEC cells significantly suppressed miR-155 expression while upregulating PTEN and DUSP14. The tube formation properties of HUVEC cells were also significantly reduced following treatment with exosomes containing miR-155 antagomirs, and these results were confirmed using CAM assay. The migration and invasion of MDA-MB-231 cells were significantly reduced after treatment with miR-155 antagomir-loaded exosomes. Conclusion It was found that miR-155 antagomir delivery using exosomes can inhibit migration, invasion, and angiogenesis via PTEN and DUSP14 in TNBC.
Keywords: PTEN